The Role of Foreign Direct Investment in Achieving Sustainable Development in Iraq: An Analytical Study for The Period of 2010-2018 - Mahdi, Haider Kadhim; Hamza, Abdulmahdi Raheem; Sabti, Yousif Mousa (South Asian Journal of Social Sciences and Humanities, 2021)
This study aims to demonstrate the role of foreign direct investment in achieving sustainable  development in Iraq. The Iraqi Investment Law No. (13) for the year 2006 and the amendments  attached to it for the years 2009 and 2015 serve as a legal cover to grant many privileges and  tax exemptions to foreign investors in order to attract more of them into the country. As Iraq is  a developing country, it is in dire need of foreign direct investment to advance its economic  and service reality by financing development programs and plans. The need for direct foreign  investments to be directed towards the productive sectors.
Keywords: Foreign direct investment; Sustainable development